2001
DOI: 10.1136/oem.58.11.702
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological study of the relations between exposure to organophosphate pesticides and indices of chronic peripheral neuropathy and neuropsychological abnormalities in sheep farmers and dippers

Abstract: Objectives-To investigate the hypothesis that chronic low level exposure to organophosphates (OPs) in sheep dips is related to clinically detectable measures of polyneuropathy. Methods-The design was a cross sectional exposure-response study of sheep dippers and other non-exposed groups. The study group consisted of 612 sheep dipping farmers, 53 farmers with no sheep dipping experience, and 107 ceramics workers. Retrospective exposure information was obtained by questionnaire based on stable and easily identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
0
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(97 citation statements)
references
References 12 publications
5
90
0
2
Order By: Relevance
“…The study also provided important insight into the profile of neurotoxicity, which confirmed earlier findings and showed that there was a positive correlation between abnormal neurological tests and evidence of anxiety and depression in patients exposed to OP. In another study , the neuropathy profile confirmed earlier observations (Kaplan et al, 1993;Steenland et al, 1994;McConnell et al, 1994;Horowitz et al, 1999;Pilkington et al, 1999) that this neuropathy linked to LTLL exposure to OP, unlike OPIDN, was predominately involving the sensory nerve fibres and affected both small and large fibre populations. This neuropathy profile linked with LTLL exposure to OP was also compared with another one seen in chronic neurotoxicity following one or more acute cholinergic episodes ).…”
Section: Referencesupporting
confidence: 84%
See 2 more Smart Citations
“…The study also provided important insight into the profile of neurotoxicity, which confirmed earlier findings and showed that there was a positive correlation between abnormal neurological tests and evidence of anxiety and depression in patients exposed to OP. In another study , the neuropathy profile confirmed earlier observations (Kaplan et al, 1993;Steenland et al, 1994;McConnell et al, 1994;Horowitz et al, 1999;Pilkington et al, 1999) that this neuropathy linked to LTLL exposure to OP, unlike OPIDN, was predominately involving the sensory nerve fibres and affected both small and large fibre populations. This neuropathy profile linked with LTLL exposure to OP was also compared with another one seen in chronic neurotoxicity following one or more acute cholinergic episodes ).…”
Section: Referencesupporting
confidence: 84%
“…A number of complicating factors, which make exposure assessment extremely difficult (Table 7, may be responsible for absence of dose Á/response relationship in some studies. Furthermore, the high quality studies did show a doseÁ/response relationship (Stephens et al, 1995;Pilkington et al, 1999).…”
Section: Studies Fail To Establish Dose á/Response Relationshipmentioning
confidence: 96%
See 1 more Smart Citation
“…Acute pesticide poisoning is followed, sometimes after many years, by impaired neurobehavioral performance and decreased nerve conduction velocity as well as increased frequency of neurologic symptoms (London et al 1998;McConnell et al 1994;Rosenstock et al 1991;Savage et al 1988;Steenland et al 1994;Wesseling et al 2002). Chronic pesticide exposure has also been associated with neurologic deficits London et al 1997;Pilkington et al 2001;Ruijten et al 1994;Sack et al 1993; Environmental Medicine | Kamel et al 1770 VOLUME 111 | NUMBER 14 | November 2003 • Environmental Health Perspectives Table 3. The referent for all comparisons is the control group; the value is 1 for digit span and 0 for other tests.…”
Section: Discussionmentioning
confidence: 99%
“…En los últimos años se han descrito cuadros neuropsicológicos crónicos no bien definidos, incluyendo el Síndrome de fatiga crónica, relacionados, en unos casos, con efectos a largo plazo de intoxicaciones agudas y, en otros, con exposiciones acumulativas subclínicas [25][26][27][28] . Este tipo de efecto no ha sido confirmado por el momento.…”
Section: Anales Sis Sanunclassified